2010
DOI: 10.1186/1476-4598-9-200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of human cancer reveals a functional role of Heme Oxygenase-1 in tumor cell adhesion

Abstract: BackgroundHeme Oxygenase-1 (HO-1) is expressed in many cancers and promotes growth and survival of neoplastic cells. Recently, HO-1 has been implicated in tumor cell invasion and metastasis. However, the molecular mechanisms underlying these biologic effects of HO-1 remain largely unknown. To identify a common mechanism of action of HO-1 in cancer, we determined the global effect of HO-1 on the transcriptome of multiple tumor entities and identified a universal HO-1-associated gene expression signature.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…Although PXDN was expressed in melanoma samples its physiological role remains largely unexplored. Silencing PXDN in mesenchymal melanoma cells blocked cellular invasion and this observation is consistent with a previous study showing that loss of PXDN in BeWo choriocarcinoma cells blocked cellular invasion and adhesion [32]. Transforming growth factor – β1 (TGF-β1) treatment induced the production of PXDN by differentiating myofibroblasts undergoing an EMT during tissue fibrosis [50].…”
Section: Discussionsupporting
confidence: 89%
“…Although PXDN was expressed in melanoma samples its physiological role remains largely unexplored. Silencing PXDN in mesenchymal melanoma cells blocked cellular invasion and this observation is consistent with a previous study showing that loss of PXDN in BeWo choriocarcinoma cells blocked cellular invasion and adhesion [32]. Transforming growth factor – β1 (TGF-β1) treatment induced the production of PXDN by differentiating myofibroblasts undergoing an EMT during tissue fibrosis [50].…”
Section: Discussionsupporting
confidence: 89%
“…Further studies are needed to address the issue of plasma LPA levels and increased AGPAT2 expression in ovarian cancer to refine the treatment and prognosis of ovarian cancer. A recent comparative meta-profiling analysis of 190 human tumors of 14 different types (breast, pancreas, lung, bladder, ovary, melanoma, uterus, renal, prostate, central nervous system, lymphoma, colorectal, mesothelioma and leukemia) identified increased expression of AGPAT2 [57]. A recent report found that knocking down AGPAT2 expression by siRNA inhibited tumor growth in an orthotopic xenograft model of human osteosarcoma [58].…”
Section: -Acylglycerol-3-phosphate O-acyltransferases In Cancermentioning
confidence: 97%
“…PXDN, a member of the larger peroxidase gene family, is an adhesion molecule involved in ECM formation (Peterfi et al 2014;Tauber et al 2010). It is one of the target genes of miR-29a.…”
Section: Relationship Between Genes' Expression and Survival In Primamentioning
confidence: 99%